Republic of Korea : Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Korea. (IMF Staff Country Reports; Country Report, 2010)
The swift and decisive policy response of Korea has contributed to an impressive economic recovery from the financial turmoil. Executive Directors welcomed the well-calibrated and gradual exit strategy while aiming to achieve strong and sustainable long-term economic growth. Directors welcomed the National Fiscal Management Plan (NFMP) and the National Debt Management Plan (NDMP). They encouraged the authorities to introduce bolder reforms to raise productivity in the nontaxable sector and also to establish Food Safety System Certification (FSSC). They suggested that increased labor market flexibility and social protection would also help facilitate the rebalancing of the economy.